Scholasticism, the dilemma for a radical reformation of our educational thought and practice - Helberg, P. J. (Koers, 1975)
Those who have acquainted themselves with the work of Prof J.A.L. Taljaard will undoubtedly agree as regards the following two issues. First of all, Taljaard, theoretically and practically, reveals a special interest in education in general as well as in the furtherance of Christian educational thought and practice). On the other hand, Taljaard has set himself the aim in his philosophical work of attaining a radical biblical approach and a radical biblical philosophy. This implies not only a profound ‘No’ to Humanism, but also an effort to get ‘reformed’ philosophy disentangled from the shackles of Scholasticism which still persists as an active power that must never be underestimated. This leads him, naturally, more than once, to a confrontation with authors of reformed philosophy and theology, who, aware of it or not, did not succeed in freeing themselves from old Scholastic influences). To fight Scholasticism, in our ‘reformed’ Christian society, demands moral courage as well as a firm belief in one’s calling. It also includes the risk of becoming alienated by those who, usually or naturally, (should) stand very close to you. This, however, is sad when viewed in terms of the confession which Taljaard never gets tired to accentuate, namely, that life is to be a religious worship of our Lord, the Creator and Redeemer in Jesus Christ.